1988
DOI: 10.1111/j.1365-2125.1988.tb03280.x
|View full text |Cite
|
Sign up to set email alerts
|

Saturation of the tubular excretion of beta‐lactam antibiotics.

Abstract: 1 The saturability of the tubular excretion of cloxacillin, benzylpenicillin and cephradine was investigated. 2 Volunteers received a continuous infusion of one of the antibiotics at increasing infusion rates in order to maintain constant plasma concentrations at three different levels. Blood and urine samples were taken every 30 min. Sufficient urinary flow was ensured by a saline infusion (500 ml h-').3 Renal clearance of the antibiotic was calculated for the non-protein bound fraction of the drug. 4 Tubular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 19 publications
4
26
1
Order By: Relevance
“…AUC cefadroxil (0 -120) or AUC inulin (0 -120) is the area under the cefadroxil or inulin plasma concentration-time curve from 0 to 120 min, as determined by the trapezoidal rule. Since cefadroxil undergoes glomerular filtration, tubular secretion (Bins and Mattie, 1988), and tubular reabsorption (Garcia-Carbonell et al, 1993) in kidney, and given the sequential expression of PEPT1 and PEPT2 in the renal proximal tubule (Smith et al, 1998;Shen et al, 1999), the drug's renal clearance can be represented as…”
Section: Chemicals [mentioning
confidence: 99%
“…AUC cefadroxil (0 -120) or AUC inulin (0 -120) is the area under the cefadroxil or inulin plasma concentration-time curve from 0 to 120 min, as determined by the trapezoidal rule. Since cefadroxil undergoes glomerular filtration, tubular secretion (Bins and Mattie, 1988), and tubular reabsorption (Garcia-Carbonell et al, 1993) in kidney, and given the sequential expression of PEPT1 and PEPT2 in the renal proximal tubule (Smith et al, 1998;Shen et al, 1999), the drug's renal clearance can be represented as…”
Section: Chemicals [mentioning
confidence: 99%
“…The kidney has a key role in the elimination of these antibiotics from plasma, since they are almost completely excreted into the urine whether administered orally or intravenously (1,2). The urinary excretion appears to be the result of two processes: glomerular filtration and secretion into the tubular lumen ( 1,3). Although the transepithelial flux of(3-lactam antibiotics has not been studied in detail, the following steps seem to be involved in the latter process.…”
mentioning
confidence: 99%
“…The experimental procedure is described in detail elsewhere (Bins & Mattie, 1988). In brief, three steady-state plasma concentrations (low, high and very high) were achieved by a combination of bolus intravenous injection plus 2.5 h i.v.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, multiple regression analysis of the tubular clearance was performed according to Scatchard using the results obtained for patients and for healthy volunteers, and using the reciprocal value of the urinary flow as an additional independent variable. For this purpose the observations from our earlier study of healthy volunteers were used (Bins & Mattie, 1988). It was shown that diuresis had no significant influence on clearance.…”
Section: Plasma Drug Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation